Wallace K. Ferguson Prize Forum Author’s Response: Barbed-Wire Imperialism: Some Canadian Connections and Contemporary Considerations - Forth, Aidan (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2021)
This article reassesses the argument of Barbed-Wire Imperialism for a contemporary Canadian readership. The concentration and segregation of indigenous communities on demarcated reserves in western Canada exhibited many of the same dynamics as British concentration camps erected in the context of colonial famines, pandemics, and guerilla warfare. As Canada encounters its own colonial past in cities like Kitchener (named after the infamous British General who detained African civilians in dirty and disease-ridden wartime camps), the colonial mantra to concentrate and control also finds resonance in Canada’s “racialized state” and in the burgeoning prisons, migrant labour facilities, and refugee camps of contemporary North America.